History of Nebraska - Naugle, Ronald C. (Ronald Clinton), 1942-; Montag, John J.; Olson, James C. (University of Nebraska Press, 2014)
Ronald C. Naugle is professor emeritus of history at Nebraska Wesleyan University. The author and editor of numerous books, he is coeditor of Nebraska Quilts and Quiltmakers and the online edition of Encyclopedia Britannica's Nebraska . John J. Montag is professor emeritus of library and information technology at Nebraska Wesleyan University. James C. Olson (1917-2005) was president emeritus of the University of Missouri. He is the author of several books, including Stuart Symington: A Life.